Effects of agricultural mechanization on economies of scope in crop production in Nigeria - Takeshima, Hiroyuki; Hatzenbuehler, Patrick L.; Edeh, Hyacinth O. (Elsevier, 2020)
Agricultural mechanization has often been associated with scale-effects and increased specialization. Such characterizations, however, fail to explain how mechanization may grow in Africa where production environments are heterogeneous even within a farm household, and crop diversification may help in mitigating risks. Using panel data from farm households and crop-specific production costs in Nigeria, we estimate how the adoptions of animal traction or tractors affect the economies of scope (EOS) for rice, non-rice grains, and legumes/seeds, which are the crop groups that are most widely grown with animal traction or tractors in Nigeria, with respect to other non-rice crops. The inverse-probability-weighting method is used to address the potential endogeneity of mechanization adoption and is combined with primal- and dual-models of EOS estimation. The results show that the adoption of these mechanization technologies is associated with greater EOS between rice and non-rice crops but lower EOS among non-rice crops (i.e., between non-rice grains, legumes/seeds, and other non-rice crops). Mechanical technologies may raise EOS between crops that are grown in more heterogeneous environments, even though it may lower EOS between crops that are grown under relatively similar agroecological conditions. To the best of our knowledge, this is the first paper that shows the effects of mechanical technologies on EOS in agriculture in developing countries.